2015
DOI: 10.1179/0039363015z.000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D laser scanning for monitoring the dimensional stability of a Byzantine ivory panel

Abstract: The British Museum has in its collections a magnificent Byzantine ivory panel. However, the panel has become warped over time and there is a join on the left side, where it has suffered a break in the past. It has been connected with two metal pins and adhesive in a previous conservation treatment but there is now concern that these could be having an adverse influence on natural movements within the ivory. Given the importance of the panel, the decision was made to leave the pins in place and monitor the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Again, the advantage of having a 3D model is that the object can be rotated to see engravings on both sides and it can be rotated to see the engraving both from the top and inverted. In addition, the texture can be removed to see the engraving without any influence of the texture, but also, if the quality of the models allows it, study bone surface modifications (Maté-González et al, 2015;Maté-González et al, 2017), monitor dimensional stability and surface degradation (Hess et al, 2015), measure curvatures (De Groote et al, 2010), etc. Figure 7: Detail of the 3D model with visible texture on top (https://sketchfab.com/3dmodels/1490299c639643ee834fe3a0cd8578ee) and ultraviolet fluorescence texture on bottom (https://sketchfab.com/3dmodels/2eef8001f89f4802ab8866806a7e7fb5).…”
Section: Engraved Antler From Trou Des Nutons (Rbins)mentioning
confidence: 99%
“…Again, the advantage of having a 3D model is that the object can be rotated to see engravings on both sides and it can be rotated to see the engraving both from the top and inverted. In addition, the texture can be removed to see the engraving without any influence of the texture, but also, if the quality of the models allows it, study bone surface modifications (Maté-González et al, 2015;Maté-González et al, 2017), monitor dimensional stability and surface degradation (Hess et al, 2015), measure curvatures (De Groote et al, 2010), etc. Figure 7: Detail of the 3D model with visible texture on top (https://sketchfab.com/3dmodels/1490299c639643ee834fe3a0cd8578ee) and ultraviolet fluorescence texture on bottom (https://sketchfab.com/3dmodels/2eef8001f89f4802ab8866806a7e7fb5).…”
Section: Engraved Antler From Trou Des Nutons (Rbins)mentioning
confidence: 99%
“…Knowledge of image-based modelling (methods of reconstructing metric models in three dimensions using visible light photography) or 3d scanning (a metric surface measurement based on the sampling of surface by laser or light) can be brought in by subject specialists, who explain their methodology and the technological kit involved, while the museum professional can contribute their knowledge of the object's specific requirements, such as climate control through RH/T, lighting conditions, exposure to UV, expected natural object movement, etc. (Hess, Korenberg et al 2015). Thus, both parties learn from the other and project outcomes are improved.2 T he motivation for encouraging knowledge exchange between academia and CH professionals is to build capacity in the CH institutions but fundamentally to enable the institutions to adopt innovative technologies to further their institutional aims.…”
Section: Nowadays Ch Institutions Can Potentially Expand Theirmentioning
confidence: 99%
“…Guidi et al [7] tested the use of 3D imaging technology to monitor wooden artworks when sudden changes occur in environmental parameters. Hess et al [8] demonstrated the potential of 3D colour laser scanning to monitor the dimensional stability of a Byzantine ivory panel. Palma et al [9] proposed a new method to quantify panel deformations, based on a non-rigid registration algorithm, by comparing 3D models acquired with different scanning devices and at different times (2002 and 2015).…”
Section: Introductionmentioning
confidence: 99%